Fathers' Parental Leave-Taking, Childcare Involvement and Mothers' Labor Market Participation - Marcus Tamm (Institute of Labor Economics (IZA), 2018)
This study analyzes the effect of fathers' parental leave-taking on the time fathers spend with their children and on mothers' and fathers' labor supply. Fathers' leave-taking is highly selective and the identification of causal effects relies on within-father differences in leave-taking for first and higher order children that were triggered by a policy reform promoting more gender equality in leave-taking. Results show that even short periods of fathers' parental leave may have long-lasting effects on fathers' involvement in childcare and housework. Effects on maternal labor supply are also significantly positive but do not persist over time.
Keywords: H31; J13; J22; 330; parental leave; childcare; female labor supply; gender differences; policy evaluation